Delimitation of hydrotopes using the example of the Polish Tatra Mountains and the southern part of Podhale - Wójcik, Sabina (Quaestiones Geographicae, 2026)
This study aimed to identify the dominant types of water circulation in the Polish Tatra Mountains and the southern part of Podhale. Using a deductive method, individual hydrotopes were separated and combined into 15 real hydrotope types. Their spatial differentiation refers to the distribution of elements of the natural environment. Infiltration type patches were characterised by a meridional course and runoff type patches in the southern part of the Tatra Mountains and the predominant part of Podhale were found to exhibit a meridional or latitudinal course. The dominant type in the study area is the evapotranspiration type.